2019
DOI: 10.1029/2018wr023650
|View full text |Cite
|
Sign up to set email alerts
|

A Nonlinear Dynamical Systems‐Based Modeling Approach for Stochastic Simulation of Streamflow and Understanding Predictability

Abstract: We propose a time series modeling approach based on nonlinear dynamical systems to recover the underlying dynamics and predictability of streamflow and to produce projections with identifiable skill. First, a wavelet spectral analysis is performed on the time series to identify the dominant quasiperiodic bands. The time series is then reconstructed across these bands and summed to obtain a signal time series. This signal is embedded in a D‐dimensional space with an appropriate lag τ to reconstruct the phase sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 73 publications
0
9
0
Order By: Relevance
“…Here we approximate the information content of daily streamflow series, an extremely complex problem well beyond the scope of this study. Credible efforts to characterize daily streamflows involve characterization of marginal distributions, spatiotemporal correlation structures, and intermittency (Papalexiou & Serinaldi, 2020), as well as climatic indices and epochal variations in predictability (Rajagopalan et al, 2019). Archfield et al (2013) argue that at least seven fundamental streamflow statistics are needed to fully characterize daily streamflow.…”
Section: Resultsmentioning
confidence: 99%
“…Here we approximate the information content of daily streamflow series, an extremely complex problem well beyond the scope of this study. Credible efforts to characterize daily streamflows involve characterization of marginal distributions, spatiotemporal correlation structures, and intermittency (Papalexiou & Serinaldi, 2020), as well as climatic indices and epochal variations in predictability (Rajagopalan et al, 2019). Archfield et al (2013) argue that at least seven fundamental streamflow statistics are needed to fully characterize daily streamflow.…”
Section: Resultsmentioning
confidence: 99%
“…(2016), Rajagopalan et al. (2019), and Sangoyomi et al. (1996) utilized it for hydroclimatic forecasting and simulation.…”
Section: Introductionmentioning
confidence: 99%
“…Jayawardena and Lai (1994) applied it to predict rainfall and SF and Delforge et al (2020) to analyze and forecast SF recessions. Erkyihun et al (2016), Rajagopalan et al (2019), and Sangoyomi et al (1996) utilized it for hydroclimatic forecasting and simulation. Also, studies that identified low-dimensional dynamics across different hydrological processes showed that complexity can emerge from a small set of governing equations, which underpins the idea that simple deterministic hydrological models can adequately describe complex hydrological processes (Procaccia, 1988).…”
mentioning
confidence: 99%
“…The different characteristics of the original real series and their DLs may be due to the noises from many sources and therefore, noise cancellation may be important for obtaining original property of the time series. On the other hand, Rajagopalan et al (2019) extracted the dominant quasi-periodic components through the wavelet analysis of the flow rate at the Lees Ferry station in the Colorado River and quantified the trajectory branching in the phase space over time using local Lyapunov exponents [20]. As a result, the flow rate of the Colorado River was revealed to be highly predictable.…”
Section: Introductionmentioning
confidence: 99%